Analisis Laju Penurunan Temperatur di Dalam Ruangan Menggunakan AC Low Watt 0,5 HP - Khambali Khambali; Listiyono Listiyono (Jurnal Energi dan Teknologi Manufaktur, 2021)
Heat absorb ability split AC is the most important factor in the cooling speed on room temperature. The rate of temperature drop is determined by many factors, including compressor power. Nowadays, there are many Split AC are produced that have low power (low Watt), so that research is needed to determine the cooling speed in a room. This study uses a low watt split AC with a power of 0.5 HP. The distance from the evaporator and the outside temperature are used as independent variables, while the rate of temperature reduction or cooling speed in the room is used as the dependent variable. The results showed that the distribution of room temperature and the rate of temperature reduction in the room varied based on the position of the distance to the location of the AC Split Low Watt. The lowest temperature and reduction rate in the room occurs at a distance of 2 m and 3 m in front of the AC location. The outside temperature or the temperature around the location of the AC condenser affects the temperature distribution at each distance in front of the AC. When the outside temperature is low, the temperature conditions at a distance of 1 m, 4 m, and 5 m have a significant difference. While the high outside temperature conditions, the temperature at a distance of 1 m, 4 m, and 5 m, namely the positions close to the wall, is almost the same. Kata kunci: AC, split, low watt, evaporator